2021
DOI: 10.3390/electronics10030235
|View full text |Cite
|
Sign up to set email alerts
|

Speech Processing for Language Learning: A Practical Approach to Computer-Assisted Pronunciation Teaching

Abstract: This article contributes to the discourse on how contemporary computer and information technology may help in improving foreign language learning not only by supporting better and more flexible workflow and digitizing study materials but also through creating completely new use cases made possible by technological improvements in signal processing algorithms. We discuss an approach and propose a holistic solution to teaching the phonological phenomena which are crucial for correct pronunciation, such as the ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 59 publications
1
14
0
Order By: Relevance
“…Repurposed tools Forvo (Pierson 2015), Lingua Libre (https://lingualibre.org/) accessed on 22 December 2023, YouGlish (McCarthy 2018) 3 Dedicated tools CAPT system for hearing impaired (Sztahó et al 2014), Inton@Trainer (Lobanov et al 2018), ELSA Speak (Samad and Ismail 2020), StudyIntonation (Boitsova et al 2018;Bogach et al 2021) Thus, in our work we strive to rise to the challenges of the personalization and customization of CAPT feedback to both the target language and the individual learners. Although most CAPT systems address a single language, our aim is to develop an environment suitable for all languages, allowing the visualizations to be tailored to the prosody of the target language.…”
Section: No Class Examples Of Toolsmentioning
confidence: 99%
See 1 more Smart Citation
“…Repurposed tools Forvo (Pierson 2015), Lingua Libre (https://lingualibre.org/) accessed on 22 December 2023, YouGlish (McCarthy 2018) 3 Dedicated tools CAPT system for hearing impaired (Sztahó et al 2014), Inton@Trainer (Lobanov et al 2018), ELSA Speak (Samad and Ismail 2020), StudyIntonation (Boitsova et al 2018;Bogach et al 2021) Thus, in our work we strive to rise to the challenges of the personalization and customization of CAPT feedback to both the target language and the individual learners. Although most CAPT systems address a single language, our aim is to develop an environment suitable for all languages, allowing the visualizations to be tailored to the prosody of the target language.…”
Section: No Class Examples Of Toolsmentioning
confidence: 99%
“…Estimating and measuring fundamental frequency and modeling the pitch produced are non-trivial tasks (Hirst and de Looze 2021), which may require an external reference to verify all of the stages. It was shown in Bogach et al (2021) how Praat software could be of much assistance when live speech recording for pitch extraction is conducted; voice activity detection algorithms are used on the raw pitch readings before the other signal conditioning stages. The latter stages include pitch filtering, approximation, and smoothing, which are standard digital signal processing stages to obtain a pitch curve adapted for pedagogic purposes.…”
Section: Speech Signal Processing and Visualizationmentioning
confidence: 99%
“…ASR technology applied to a CALL context has been criticized by some authors in the past decade due to its incapacity to comprehend L2 speech accurately at a similar rate as human listeners (DERWING; MUNRO; CARBONARO, 2000;KIM, 2006;LEVIS;SUVOROV, 2013), its much lower accuracy scores for nonnative speakers than those for native speakers (ASHWELL; ELAM, 2017; ROGERSON-REVELL, 2021), and its insufficient or even incorrect feedback (CHEN, 2011;DE-MENKO;WAGNER;CYLWIK, 2010;LEVIS;SUVOROV, 2013;ROGERSON-REVELL, 2021). On the other hand, recent research has shown that this technology has been improving in the past years (ASHWELL; ELAM, 2017;DIZON, 2020;DIZON;TANG, 2020;MCCROCKLIN;EDALATISHAMS, 2020;MOUSSALLI;CARDOSO, 2020;BOGACH et al, 2021). Furthermore, Ashwell and Elam (2017, p. 61) argue that "these systems are continually improving on their respective accuracy rates by constantly gathering acoustic information and utilizing machine learning".…”
Section: Automatic Speech Recognition and Its Affordances For Pronunc...mentioning
confidence: 99%
“…Some ASR technologies provide feedback in the form of verbal descriptions and articulation charts. This feedback can improve learners’ pronunciation gradually and enhance the accuracy of segmentation ( Bogach et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%